2019
DOI: 10.4103/jnrp.jnrp_309_18
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Behavior and Treatment Needs among Drug Addicts and Controls in Amritsar District: A Case-controlled Study

Abstract: Background: Substance and drug abuse is associated with severe psychosocial problems, violence and health complications. Aims: The aim of the study was to evaluate and compare the oral hygiene status and sugar eating patterns among drug addicts with their age, gender and socio-economic status matched controls. Settings and Design: The present study comprised of two groups-Group A comprised of 100 drug addicts and Group B included 100 controls. The study sample were interviewed and subjected to a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
(37 reference statements)
1
12
0
2
Order By: Relevance
“…A similar pattern was observed for poly-drug users, more D (+3.5) and M (+3.4) teeth and fewer (À2.1) FT than controls. More recent studies among crack cocaine users [21], opioid users [24,27] and cannabis users [25] reported similar findings. Notably, a deviant finding was reported from a sample of morphine-dependent men in 1945; dental caries prevalence was quite similar to that in a control group [33], but this may reflect that caries experience in the general population at that time was very high.…”
Section: Epidemiologysupporting
confidence: 59%
See 1 more Smart Citation
“…A similar pattern was observed for poly-drug users, more D (+3.5) and M (+3.4) teeth and fewer (À2.1) FT than controls. More recent studies among crack cocaine users [21], opioid users [24,27] and cannabis users [25] reported similar findings. Notably, a deviant finding was reported from a sample of morphine-dependent men in 1945; dental caries prevalence was quite similar to that in a control group [33], but this may reflect that caries experience in the general population at that time was very high.…”
Section: Epidemiologysupporting
confidence: 59%
“…Increased risk of other oral health problems is also reported. Baghaie and colleagues [20] identified 28 primary studies examining oral health problems in illicit drug users and controls, and 10 additional primary studies [21][22][23][24][25][26][27][28][29] were identified from more recent reviews [2,[30][31][32] and further literature searches. These 38 studies were conducted in 16 different countries.…”
Section: Epidemiologymentioning
confidence: 99%
“…Hyperactivity of dopamine may be related to psychiatric symptoms such as hallucinations and delusions. It may explain the clinical features that are prone to psychiatric symptoms when a large amount of ATS is abused (acute poisoning), and the psychiatric symptoms will be relieved quickly after stopping drug abuse [19][20]. In addition, methamphetamine also induces nerve excitotoxicity through glutamate and NMDA receptors [21][22].…”
Section: Characteristics Of Ats Use Obstaclesmentioning
confidence: 99%
“…Однак, поряд із досягненням ефекту знеболення, довготривале використання опіоїдів обумовлює узалежнення та негативні медико-соціальні наслідки [3,4]. Необхідно також враховувати залежність фармакологічного ефекту від дозування препарату, від чого залежить вплив опіоїдного середника на метаболізм, зумовлюючи особливості механізмів патогенезу в різних органах і системах [5,6,7,8,9].…”
Section: вступunclassified
“…Слід відмітити, що зловживання наркотичних речовин провокує розвиток специфічних змін тканин і органів ротової порожнини із прогресуванням агресивних форм захворювань пародонту [10,11]. З метою підвищення ефективності лікування наркозалежних осіб, ряд авторів рекомендують застосовувати етіотропну та патогенетичну терапію [5,12,13]. З метою зменшення рівня мікробної колонізації у ротовій порожнині при розвитку та прогресуванні запальних захворювань пародонту, доцільним вважають застосовувати антибактеріальну терапію [11].…”
Section: вступunclassified